2018
DOI: 10.1111/agec.12462
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of multiperil crop insurance on Indonesian rice farmers and production

Abstract: This article analyzes the effect of multiperil crop insurance policy for risk-averse Indonesian rice farmers located in Tuban and Gresik Regencies of the East Java Province. Based on the model, comparative static analysis of a change in policy variables (coverage levels and premium subsidies) on input use through the coupling, wealth, and insurance effects are presented. The comparative static results are largely ambiguous and left as empirical questions. Consequently, the model is numerically simulated to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…Different crops may be chosen while crops in the same district may be planted at different times, to different varieties, on different soils and under different management practices. The markets have long been afflicted by adverse selection (Just, Calvin, & Quiggin, 1999) and possibly also moral hazard concerns (Babcock & Hennessy, 1996;Fadhliani, Luckstead, & Wailes, 2019;Smith & Goodwin, 1996). Technological innovation further diminishes an insurance company's capacity to rate by way of loss experience.…”
Section: Introductionmentioning
confidence: 99%
“…Different crops may be chosen while crops in the same district may be planted at different times, to different varieties, on different soils and under different management practices. The markets have long been afflicted by adverse selection (Just, Calvin, & Quiggin, 1999) and possibly also moral hazard concerns (Babcock & Hennessy, 1996;Fadhliani, Luckstead, & Wailes, 2019;Smith & Goodwin, 1996). Technological innovation further diminishes an insurance company's capacity to rate by way of loss experience.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs through a shift toward riskier crops. Fadhliani, Luckstead, and Wailes () examine crop insurance demand by risk averse Indonesian rice farmers. Their empirical analysis showed that crop insurance purchases result in a decline in expected yield through reductions in input use and that higher subsidy rates amplify the reduction in input use and yield.…”
Section: Moral Hazard and Prevented Plantingmentioning
confidence: 99%
“…The development of food crops by expanding the planting area is carried out by 1) printing new land (rice fields); 2) land optimization by increasing the crop index (PI); 3) optimization of another agricultural land; and 4) optimization of abandoned land (Choi et al, 2019;Junaidi et al, 2020;Neilson et al, 2020;Wicke et al, 2011). The efforts made by the government do not seem to have achieved optimal results, where the achievement of rice production is relatively insignificant compared to the rate of population increase, and there is a tendency for rice production to have a declining pattern in recent years (Fadhliani et al, 2019;Graham et al, 2020;Maraseni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%